2017
DOI: 10.1213/ane.0000000000002104
|View full text |Cite
|
Sign up to set email alerts
|

Cancellation of Elective Cases in a Recently Opened, Tertiary/Quaternary-Level Hospital in the Middle East

Abstract: Case cancellations have a negative financial impact due to revenue loss and the potential costs of underutilized time. The goals of this study at a recently opened hospital in the Middle East were to measure the cancellation rates for elective surgical or endoscopic cases and to identify the reasons for cancellation. During the 1-month study period, 170 (22.4%) of the 760 scheduled cases were cancelled. Cultural norms and patient no-shows on the day of surgery accounted for the majority of case cancellations. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
21
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 16 publications
2
21
0
2
Order By: Relevance
“…Similar to what has been reported in the literature, the majority of our cancellations (71.4%) were considered avoidable . Patient‐related factors, such as patient no‐show and facility‐related cancellations due to lack of OR time or hospital bed availability, have been most commonly reported as causes of late surgical cancellations . However, in our study, work‐up/medical causes (21 of 35, 60%) were the most common cause of cancellations within 24 hours of scheduled surgery, whereas patient‐related factors accounted for only 14.3% (5 of 35) of cancellations, probably attributable to our specialized patient population and associated complex medical conditions.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Similar to what has been reported in the literature, the majority of our cancellations (71.4%) were considered avoidable . Patient‐related factors, such as patient no‐show and facility‐related cancellations due to lack of OR time or hospital bed availability, have been most commonly reported as causes of late surgical cancellations . However, in our study, work‐up/medical causes (21 of 35, 60%) were the most common cause of cancellations within 24 hours of scheduled surgery, whereas patient‐related factors accounted for only 14.3% (5 of 35) of cancellations, probably attributable to our specialized patient population and associated complex medical conditions.…”
Section: Discussionsupporting
confidence: 86%
“…Previous studies evaluating surgical cancellations across all specialties have reported late cancellation rates ranging from 0.5% to 40%, varying widely based on type of hospital system (private vs public), surgical setting (inpatient vs outpatient), patient population (adult vs pediatric), and type of surgery . Of note, otolaryngology cases specifically have been reported to have high rates of late surgical cancellations, ranging from 12% to 42% .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…While several studies have evaluated the causes of bed pressures and failures of hospital trusts to meet the emergency department 4 hour performance target11 12 and others have evaluated the reason for elective cancellations across a range of healthcare settings,13 14 very little information is available on the psychosocial impact of cancellations of elective operations on patients. Others have reported on measures to reduce same day cancellations of elective operations, but have focused on other aspects, such as ensuring fitness for surgery, preventing the scheduling of the wrong operation or preventing incomplete preoperative assessments rather than addressing cancellations due to a lack of beds 15.…”
Section: Discussionmentioning
confidence: 99%
“…The same day case cancellation refers to any surgical case that is scheduled into the operation theatre list on the day before surgery but is not operated on as per the schedule [ 1 , 2 ].…”
Section: Introductionmentioning
confidence: 99%